Efek Perlakuan Kombinatif Plasma Medis dan Ekstrak Daun Binahong Terhadap Penyembuhan Luka Fase Proliferasi Pada Mencit Diabetik - Wahyuningtyas, Eka Sakti; Nasruddin, N; Rahayu, Heni Setyowati Esti; Lutfiyati, Heni; Sikumbang, Isabella Meliawati; Nurani, Laela Hayu; Kartikadewi, Arum; Salsabila, Nia; Putri, Gela Setya Ayu; Kurniasiwi, Putri; et al. (Prosiding University Research Colloquium, 2020)
Plasma medicine is a relatively new and multidisciplinary study involving the study of plasma science, biomedicine, pharmacy, and other health sciences to utilizing plasma for medical therapy. Plasma is the fourth substance, after solids, liquids, and gases. Plasma can produce biological molecules of Reactive Oxygen and Nitrogen Species (RON) which, if controlled in the right dose, can be beneficial for health. This animal study examines the effect of combinative treatment of medicine plasma and binahong leaf extract on proliferation phase wound healing in a diabetic test model. The study used Balb mice 7-8 years old which were induced by STZ with acute wounds which were divided into 4 groups, namely the wound group of diabetic mice without treatment (C), the group of diabetic mice with the treatment of binahong leaf extract (B), the group of combined treatment wounds plasma jet (P) and the wound group of diabetic mice treated with a combination of plasma and, binahong leaf extract (PB). Binahong leaf extract concentration 1% in DMSO solvent. The jet type medicine plasma treatment was carried out every day from day 0 to day 6. Macroscopic observation of the wound was carried out every day from day 0 to day 7. On day 7 it appears that the size of the wound area for P is much smaller than for C, B, and PB. The size of area B and PB is relatively the same, but smaller than C. The results of this study indicate that the binahong leaf extract tends to inhibit the performance of medicine plasma in accelerating the healing of the proliferation phase.